Genome-Wide Analysis of Genetic Diversity in Plasmodium falciparum Isolates From China–Myanmar Border - Ye, Run; Tian, Yini; Huang, Yufu; Zhang, Yilong; Wang, Jian; Sun, Xiaodong; Zhou, Hongning; Zhang, Dongmei; Pan, Weiqing (Frontiers in Genetics, 2019)
Plasmodium falciparum isolates from China-Myanmar border(CMB) have experienced regional special selective pressures and adaptive evolution. However, the genomes of Plasmodium falciparum isolates from this region to date are poorly characterized. Herein, we performed whole-genome sequencing of 34 P. falciparum isolates from CMB and a series of genome-wide sequence analyses to reveal their genetic diversity, population structures and comparisons with the isolates from other epidemic regions (Thai-Cambodia border, Thai-Myanmar border and West Africa). Totally 59,720 high quality SNPs were identified in the P. falciparum isolates from China-Myanmar border, with average nucleotide diversity (π=4.59 x 10-4) and LD decay (132bp). The Tajima’s D and Fu & Li’s D values of the CMB isolates were -0.8 (p<0.05) and -0.84 (p<0.05), respectively, suggesting a demographic history of recent population expansion or purifying selection. Moreover, 78 genes of the parasite were identified that could be under positive selection, including those genes conferring drug resistance such as Pfubp-1. In addition, a 33 SNPs were identified for tracing the source of the parasites with a high accuracy by analysis of the most differential SNPs among the four epidemic regions. Collectively, our data demonstrated high diversity of the CMB isolates’ genomes forming a distinct population and the identification of 33 SNP barcode provides a valuable surveillance of parasite migration among the regions.